Association of serum 25-hydroxyvitamin D in COVID-19: A study from India - Naveenreddy, Samala; Chaudhuri, Jaydip Ray; Mridula, Kandadai Rukmini; Balaraju, Banda; Bandaru, VCS Srinivasarao (Nepal Mediciti Medical Journal, 2021)
Background: Novel coronavirus infection 2019 (COVID-19), a pandemic has affected patients irrespective of gender and age. Existing studies have incriminated low levels of serum 25-hydroxyvitamin D to be associated with COVID-19 infection. The present study was to investigate serum 25-hydroxyvitamin D levels in patients with COVID-19 infection. Methods: We recruited prospectively 175 consecutive COVID-19 patients from the Department of Medicine, Yashoda hospital Hyderabad during the study period from May 2020 to December 2020. We measured in all patients, serum levels of 25-hydroxyvitamin D, calcium, phosphorus, alkaline phosphatase, C-reactive protein (CRP), D-Dimer, interleukin-6, procalcitonin, and ferritin. Results: Out of 175 patients 122(69.7%) were men, mean age was 57.2±13.6 years. Clinical symptoms were fever in 175 (100%) dry cough in 110(62.8%), tiredness in 105(60%), shortness of breath in 94(53.7%), and mechanical ventilator support requirement at admission in 40(22.8%). Serum 25-hydroxyvitamin D deficiency was noted in 108(61.7%), CRP was positive in 119(68%), abnormal D-dimer levels in 96(54.8%), abnormal procalcitonin levels in 107(61.1%) abnormal interleukin-6 levels in 98(56%), abnormal serum ferritin levels in 106 (60.5%) and overall mortality in 13(7.4%). Older age (p =0.006) hypertension (p=0.02), diabetes (p=0.01), CRP positivity (p< 0.0001) and mortality (p=0.03) were significantly associated with serum25-hydroxyvitamin D deficiency in COVID-19 patients. Serum 25-hydroxyvitamin D deficiency and age >60 years were significant predictors of mortality with odds of 7.4; (95%CI: 1.10-56.36) and 2.8: (95%CI: 0.81-9.50) respectively. Conclusion: In our study, serum 25-hydroxyvitamin D deficiency was seen in 61.1%, low levels of serum 25-hydroxyvitamin D was independently associated with >60 years age group and mortality in COVID-19.